Removal of (Crystal Violet, Janus Green) dyes by poly acrylic acid hydrogel beads - M Ali, Nooraldeen (University of Thi-Qar Journal of Science, 2023)
Removal of Crystal Violet (C.V) and Janus Green (J.G) dyes was involved when using poly acrylic beads as a surface. The Isotherm of the process were studied and factor that influence it such as (Temperature, ionic strength , Shaking effect , effect of dry beads ) in addition to mixing dyes . According to the results it has been found that the adsorption of the two dyes is matched of the friendlish equation more than the Temkin and Langmuir equation. there is an a positive relationship between the adsorption and increasing of temperature found that the adsorption increasing when the temperature increase . the adsorption increased when the salt added at temperature (20C0). Also, There is a small change when used a wet beads of poly acrylic. adsorption is increasing at shaking when we compare with no shaking of water bath. thermodynamic function were studied (ΔH,ΔG,ΔS) to explain that the process are emitter or absorbent also spontaneous and the random of the process . a kinetic parameter has been studied Lagergren equation ( first order) and by (second order) equations, depending to the results of the experimental, data shown us that the adsorption obeys the pseudo-second order furthermore the first-order equation .